(untitled) (Texas Journal of Engineering and Technology, 2022)
The article discusses ways to solve the problem of developing the scientific potential of the student’s personality. These ways are in line with the general tasks of student development. The peculiarity of the development of scientific potential is associated with the solution of the problems of scientific certification of the training course and the criteria for selecting the content for its construction.